A clinicopathological study on fungal infection in nasal polyposis - Paventhan, K.; Lakshmi Narayana, M.; P. N., Aswin Vaishali (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Nasal polyposis is a multifactorial disease. Despite the presence of numerous theories proposed towards the aetiology of nasal polyp, inflammation is the main causative factor. Fungi can impair the local immune system and bring about an inflammatory response causing polyp formation. The aim and objective of the research was to know the prevalence of fungal infection in nasal polyposis and to assess the microbiological and pathological features of fungi in nasal polyposis. Methods: A total of 100 patients operated for nasal polyposis were included in the study excluding immune-compromised patients. All the nasal polyposis cases were subjected to clinical examination, diagnostic nasal endoscopy and medical treatment before undergoing surgical treatment. Polyps removed were subjected to histopathological examination (HPE) and potassium hydroxide (KOH) wet mount examination under microscope. Results: Out of the 100 patients studied 66 patients (66%) were in the age group between 31 to 60 years. 85 patients had bilateral polyps, in which fungal element was isolated in 11 patients and among 15 patients with antrochoanal polyp 1 patient had fungal isolates. Of the 17 patients who had previous history of surgery, fungi were isolated in 4 patients and the rest were from patient who got operated for the first time. 3 out of the 8 patients, who had recurrence, were positive for fungal infection. Conclusions: Fungi are found to be more prevalent in nasal polyps and fungi can be considered as one of the main causative factor for formation of nasal polyposis and its recurrence after surgery. Anti-fungal agents could be a helping hand in the management of nasal polyposis to prevent its recurrence.